A Delicate Balance Portfolio Analysis and Management for Intelligence Information Dissemination Programs - Landree, Eric (RAND Corporation, 2009)
This description of the application of the RAND Corporation's PortMan portfolio analysis and management method and Delphi consensus-building method for the National Security Agency (NSA) Information Sharing Services (ISS) division highlights how these methods enable the data-driven analysis of project portfolios and the allocation of research and development (R&D) and operations and maintenance (O&M) resources according to value, risk, and cost.